Analysis of moderation between social factors and consumer behaviour - Rodríguez Vásquez, Lady Geovanna; Feijoo Jaramillo, Irene; Sarmiento Chugcho, Carlos (Revista Universidad de Guayaquil, 2024)
The main objective of this research is to analyse how the level of experience and age influence the relationship between social factors and consumer behaviour in mixed shopping canters. The approach used in this research is quantitative at a descriptive, correlational level whose sample was 300 individuals. The exploratory study at KMO= 0.70. The results revealed a positive and significant moderating impact of experience levels on the relationship between the factors (b=0.27, t=-4.61, p˂.001), which supports H1. Regarding H2, the results reveal a non-significant positive moderating impact of experience levels (b=0.01, t=-0.03, p=0.896), not being enough to support H2. Analyses showed that the effect was stronger at low levels of experience, fading as experience increased, on the other hand, as age level increased the strength of the relationship between social factor and consumer behaviour.
Keywords: Social factor; consumer behavior; level of experience and age